Epidemiologic Features and Surgical Treatment of Spontaneous Pyogenic Spondylodiscitis in Bangladesh - Alam, Md Shafiul; Haroon, Kaisar; Islam, Abu Md Mofakhkharul; Raihan, Md Farid; Farzana, Tayseer; Hasan, Rejaul; Karim, Md Rezaul; Islam, Joynul (Bangladesh Journal of Neurosurgery, 2022)
Background: Spontaneous pyogenic spondylodiscitis is an uncommon clinical condition. But in our country it is not infrequent. High level of clinical suspicion is necessary for diagnoses of spontaneous pyogenic spondylodiscitis. There is no study regarding this issue in Bangladesh. Objective: The objective of this study was to see the epidemiological feature and types of surgical treatment of spontaneous pyogenic spondylodiscitis in Bangladesh Materials and Methods: This is a retrospective observational study. This study was done in the Department of Neurosurgery, National Institute of Neurosciences and Hospital, Dhaka, Bangladesh. The study period was January, 2016 to July, 2021 for a period of 5.5 years. 17 patients who were undergone surgery included in the study. The data were collected from questionnaires and hospital records and analyzed. Results: In our study the highest incidence was found in 4th (23.52%) and 6th (29.42%) decade of life which was around 53%. The male to female ratio was about 2: 1.The present study showed the most common involvement was in lumbar region (35.31%), in dorsal and sacral region it was 23.52% and the cervical region in 17.65%. Regarding surgical treatment in cervical region both anterior (with fixation) and posterior approach was done, in dorsal, lumbar and sacral region posterior approach with or without fixation was done. Conclusion: In Bangladesh the incidence of Spontaneous pyogenic spondylodiscitis is relative high. It is more common in advance age with male predominance. Most frequently affected region was lumber. Surgical technique was individualized for every case. Bang. J Neurosurgery 2022; 11(2): 64-69